Activities of Greek Banks in Balkan Countries: A Comparative Balance Sheet and Income Analysis Between Affiliate Banks in Balkan Countries - Simeon Karafolas (European Regional Science Association (ERSA), 2006)
The paper proposes a comparative analysis of the activities and income of Greek banks in the Balkan countries (Albania, Bulgaria, FYROM, Romania and Serbia) by examining the balance sheet and the statement of income within the period of 2000-2004. Greek bank have a strong presence in the Balkan countries that begun the decade of '90. Their presence took the form of affiliate bank and branches. The paper examines activities through affiliate banks and parent banks for which balance sheet and income data are available. Results show differentiations of Greek banks especially with regard activities with non bank-clients and interbank activities in assets and liabilities as well. Non-bank activities arise to 80% in some cases, which represents a strong confidence to these banks. Differentiations between affiliates and with regard parent bank are presented to income and profitability results as well.
Keywords: 330